On the design of automatic voice condition analysis systems. Part I: Review of concepts and an insight to the state of the art. (May 2019) - Gómez-García, J.A.; Moro-Velázquez, L.; Godino-Llorente, J.I.
Highlights: Introductory concepts in the automatic voice condition analysis field are presented. A systematic literature review of the methodologies used in the field are introduced. A prototypical automatic voice condition analysis system is described. Variability factors affecting the performance of these systems are discussed. Abstract: This is the first of a two-part series devoted to review the current state of the art of automatic voice condition analysis systems. The goal of this paper is to provide to the scientific community and to newly comers to the field of automatic voice condition analysis a resource that presents introductory concepts, a categorisation of different aspects of voice pathology and a systematic literature review that describes the methodologies and methods that are mostly used in these systems. To this end, pathological voice is firstly described in terms of perceptual characteristics and its relationship with physiological phenomena. Then, a prototypical automatic voice condition analysis system is described, discussing each one of its constituting parts and presenting an in-depth literature review about the methodologies that are typically employed. Finally, a discussion about some variability factors that affect the performance of these systems is presented.